Facetas Indiretas e Laminados cerâmicos: uma revisão de literatura. - PENNA, Caroline Zopollato (2021)
The standard of what is aesthetically beautiful varies in time and space and, dentistry is constantly seeking to improve dental esthetics to meet these standards. In this sense, dental requirements have motivated research into new techniques that optimize the quality of form and function of the dental element, always innovating to provide the esthetics sought by society. Therefore, in the field of esthetics dentistry, dental veneers and ceramic laminates are one of the most sought after procedures, as they are treatments that result in esthetic and functional improvement for the patient. The excellence of the results make these procedures well spread in the media, as there are numerous influencers artists who present these types of restorations. And as for esthetic procedures, in general, they make patients very satisfied, as they have excellent color stability, durability and biocompatibility with the periodontium, reestablishing the self-confidence and self-esteem of the patients’ smile. Give the above, this work proposed to carry out a literature review on dental veneers and ceramic laminated, emphasizing their definitions history of emergence development, indications, contraindications, advantages, disadvantages, success rate of procedures and description of techniques from preparation to cementation, in order to better clarify and discuss these topics, based on literary woks published recently and of great importance to dentistry. Therefore, after performing the literature review, it can be concluded that, when dental veneers and ceramic laminates present failures, the main cause is incorrect planning, which ranger from error in the indication of the procedure to poor choice and mistaken execution of the technique of preparation, which can lead to accentuated pigmentation and even, invasion of the vestibular space by the veneers. Thus, given the growing demand for these esthetic dental procedures, more studies should be carried out on them, in order to bring better results and practicality for both the professional and the patient.